2011
DOI: 10.1371/journal.pone.0022839
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA 144 Impairs Insulin Signaling by Inhibiting the Expression of Insulin Receptor Substrate 1 in Type 2 Diabetes Mellitus

Abstract: BackgroundDysregulation of microRNA (miRNA) expression in various tissues and body fluids has been demonstrated to be associated with several diseases, including Type 2 Diabetes mellitus (T2D). Here, we compare miRNA expression profiles in different tissues (pancreas, liver, adipose and skeletal muscle) as well as in blood samples from T2D rat model and highlight the potential of circulating miRNAs as biomarkers of T2D. In parallel, we have examined the expression profiles of miRNAs in blood samples from Impai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
335
2
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 367 publications
(362 citation statements)
references
References 68 publications
17
335
2
8
Order By: Relevance
“…The impaired insulin and insulin-like growth factor signaling contributes to AD-associated neuronal loss, synaptic disconnection, hyperphosphorylation, and A␤ accumulation (55). Similarly, miR-144 is also increased and impairs insulin signaling through down-regulation of insulin receptor substrate 1 (56) in impaired fasting glucose and Type 2 diabetes mellitus patients. This suggests the importance and multiple implications of miR-144 in the pathogenesis of sporadic AD.…”
Section: Discussionmentioning
confidence: 99%
“…The impaired insulin and insulin-like growth factor signaling contributes to AD-associated neuronal loss, synaptic disconnection, hyperphosphorylation, and A␤ accumulation (55). Similarly, miR-144 is also increased and impairs insulin signaling through down-regulation of insulin receptor substrate 1 (56) in impaired fasting glucose and Type 2 diabetes mellitus patients. This suggests the importance and multiple implications of miR-144 in the pathogenesis of sporadic AD.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, a decrease in miR-15a, miR-29b, miR-126, and miR-223 and an increase in miR-28-3p levels in plasma indicated the manifestation of disease, indicating their value for predicting T2D. Karolina et al (2011) identified miR-144, miR-146a, miR-150, and miR-182 in the blood of T2D patients as the signature miRNAs for predicting of T2D. In addition, Pescador et al (2013) showed that three serum miRNAs (miR-138, miR-376a, and miR-15b) are potential biomarkers for distinguishing obese patients from obese-T2D and T2D patients; meanwhile, the combination of miR-503 and miR-138 can distinguish diabetic from obese-diabetic patients.…”
Section: Pkb (Akt) Signaling (Insulin Sensitivity)mentioning
confidence: 98%
“…In breast cancer, miR-378* upregulation results in an increase in cell proliferation and lactate production, and a repression of tricarboxylic acid cycle and oxygen consumption, indicating that miR-378* is able to mediate metabolic shift in cancer cells 20 . It has also been reported that hepatic miR-378/378* expression is dysregulated in a rat model of type 2 diabetes and obese mouse models, including genetic ob/ob mice and mice fed a high-fat diet 15,21,22 . However, whether and how miR-378 or miR-378* plays a regulatory role in hepatic glucose and lipid metabolism remains unclear.…”
mentioning
confidence: 98%